Proceedings of the second Western Atlantic turtle symposium, October 12-16, 1987, Mayaguez, Puerto Rico. - Ogreen, L. (ed.). (Panama City, Florida U.S. Dept. of Commerce, National Oceanic and Atmospheric Administration, National Marine Fisheries Service, Southeast Fisheries Center, Panama City Laboratory, 1989)
NOAA technical memorandum NMFS-SEFC ; 226
Keywords: Marine turtle